Optimising Inventory Turnover to Increase Profitability: A Case of Bayongbong Independent Village Unit Cooperative - Rachmat, Ade Dian Nuridha; Hadiyanti, Ami Cahya Utami (Manunggal Halim Jaya, 2023)
This study is motivated by the importance of efficient inventory management in supporting the profitability of a company, especially in the livestock cooperative sector. The purpose of this study was to analyse the effect of inventory turnover on profitability at Koperasi Unit Desa Mandiri Bayongbong. This research uses a quantitative approach with descriptive and associative research designs. The population in this study is all data related to inventory turnover and cooperative profitability covering 2016-2021, with sampling techniques using secondary data taken from the cooperative's financial statements. The analysis technique used is simple regression analysis, correlation test, and coefficient of determination. The results showed that inventory turnover had no significant effect on profitability, with a very weak and negative correlation between the two variables. This suggests that other factors, such as product quality and external factors, have more influence on the rentability of the co-operative. The implication of this study is that it is important for cooperatives to consider other aspects besides inventory management in improving profitability, such as pricing policies and more effective product marketing.